The prototype for measuring the height and monitoring of river water quality based on the Internet of Things - Sofyan Radit Kurniawan; Syamsudduha Syahrorini (Universitas Muhammadiyah Sidoarjo, 2021)
Abstract. Technology continues to develop from year to year which aims to simplify human work or automation of a system. The concept of measuring the water level is automatically applied to the river in front of the Tanggulangin tourism market, which aims to make it easier for residents to check the river water level in real time via the internet network. By utilizing the DS18B20 sensor to find out the temperature which has 97.85% accuracy and the HC-SR04 ultrasonic distance sensor which has 100% accuracy at a distance of less than 20 CM to find out the water level based on changes in the distance value on the sensor as an indication of the rise and fall of river water. From the sensor, the sensor is controlled with the Arduino UNO and NodeMCU microcontroller board to make the system work automatically, as well as the use of the MIT App Inventor to create android applications and to support the internet of things system. From the results of this research, it is obtained: (1). In the HC-SR04 ultrasound sensor test, the stability of the measurement value is very good, seen from the standard deviation value. (2). In testing the DS18B20 temperature sensor with a standard thermometer ratio has a difference of 0.7 ° C accuracy with an accuracy of 97.85% so that it can be used as a measurement tool. (3). On the TDS sensor, the standard deviation can be between 130-141 ppm which indicates this tool can function properly. (4). On the LCD, it can work properly and is ready to use in a system that functions to display information carried out by the microcontroller. (5). For pH sensors, this sensor can measure the degree of acidity / basicity of water between 1-10 pH.